The The Effect of Guided-Imagery and Oxytocin Massage on Breast Milk Production in Post Partum Mothers - Nabilla Abel Tantri Tantri; Koekoeh Hardjito; Finta Isti Kundarti; Rahajeng Siti Nur Rahmawati (Oksitosin : Jurnal Ilmiah Kebidanan, 2025)
The global exclusive breastfeeding rate is only 44%, many factors influence failure of exclusive breastfeeding, problem breast milk production contributes to breastfeeding failure. Guided-Imagery is alternative therapy in overcoming stress with minimal cost and minimal side effects, in addition to reducing stress, this therapy can reduce fatigue as well. Oxytocin massage is another alternative to overcome the problem of breast milk production. Oxytocin massage can stimulate oxytocin hormone needed in the process of breast milk production, besides that it can also provide a sense of comfortable to mother and reduce fatigue. This study used Quasy Experimental method with pretest-posttes control group design involving 52 respondents divided into an intervention group (26 respondents) who were given combination of guided-imagery and oxytocin massage 1x in day for 14 days, and a control group (26 respondents) with the purpose of Analyzing the effect of combination of guided imagery and oxytocin massage on breast milk production. Mann-Whitney test showed that significant increase in breast milk production in the intervention group (p = 0.000) after treatment. However, control group did not showed an increase in breast milk production. So, the combination of guided-imagery and oxytocin massage effective in increasing breast milk production in postpartum mothers.